Service level agreement for distributed services: a review - Alhamad, Mohammed; Dillon, Tharam; Chang, Elizabeth (IEEE Computer Society, 2011)
Cloud computing has change the strategy of the way of providing distributed services for many business and government agents. Cloud computing delivers a scalable and on demand services for most users in different domains. This new technology brings many challenges to service providers and customers especially for users who already own complicated legacy systems. This paper examines challenges related to the concepts of trust, SLA management, and cloud computing. We focus on SLA definition in cloud computing to achieve the aim of presenting a clear structure of SLA for cloud users and improve the way of building trustworthy relationship between service provider and customer. In this paper, we start with the presenting the importance of cloud computing and the need of SLA for cloud computing. Then, survey of cloud computing architecture is provided. Then, we discuss existing frameworks of service level agreements in different domains such as web services and grid computing. The last part of literature review discusses advantages and limitations of performance measurement models in SOA, distributed systems, grid computing, and cloud services. Finally, we summarize and conclude our work.